Snake venom ophthalmia and blindness caused by the spitting cobra (Naja nigricollis) in Nigeria. - Warrell, D; Ormerod, L (1976)
Venom entered the eyes of 9 patients spat at by the spitting cobra, Naja nigricollis. In 5 the only effect was a simple conjunctivitis but 4 had corneal ulceration, 1 developed anterior uveitis indicating absorption of venom in the anterior chamber, and 2 were permanently blinded. Treatment of this rare emergency is discussed: immediate irrigation of the eye with water, careful examination for corneal abrasion, and prevention of secondary infection are recommended. The value of local specific antivenom is unproven.